2021
DOI: 10.3390/ijms221910257
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of Force Generation and Nuclear Collapse in Apoptotic Cells

Abstract: Apoptosis, or programmed cell death, is a form of cell suicide that is extremely important for ridding the body of cells that are no longer required, to protect the body against hazardous cells, such as cancerous ones, and to promote tissue morphogenesis during animal development. Upon reception of a death stimulus, the doomed cell activates biochemical pathways that eventually converge on the activation of dedicated enzymes, caspases. Numerous pieces of information on the biochemical control of the process ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Morphological changes such as cell shrinkage, bubble formation in the membrane, chromatin condensation and nuclear fragmentation are observed during the apoptosis process in cells ( Monier & Suzanne, 2021 ). In the morphology of RT-4 cells stained with Giemsa solution, we observed an increase in cytoplasmic shrinkage, nuclear condensation, fragmentation and apoptotic body formation with increasing doses of cisplatin, gemcitabine and proTAME.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes such as cell shrinkage, bubble formation in the membrane, chromatin condensation and nuclear fragmentation are observed during the apoptosis process in cells ( Monier & Suzanne, 2021 ). In the morphology of RT-4 cells stained with Giemsa solution, we observed an increase in cytoplasmic shrinkage, nuclear condensation, fragmentation and apoptotic body formation with increasing doses of cisplatin, gemcitabine and proTAME.…”
Section: Discussionmentioning
confidence: 99%
“…These results verified that HeLa cervical cancer cells but not 3T3 noncancerous cells are susceptible for cellular stresses in response to MC extract. Nuclear fragmentation is a distinctive characteristic of dyeing cells, especially the ones undergoing apoptotic cell death [ 36 ]. As we anticipated, when MC extract-treated HeLa cells were stained with Trypan blue and counted for the proportion of dead cells, we found that MC extract significantly induced percent cell death in a time-dependent fashion over the course of 48 h. Further investigation at the molecular level indicated that MC extract induced HeLa cervical cancer cell death through activation of caspase-dependent pathway which is a major route of apoptotic cell death [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A time-course experiment will resolve this question. The activation of endonucleases during apoptosis results in the fragmentati nuclear DNA [31]. In the later steps of cell death, chromosomal DNA is cleaved smaller fragments through the action of endonucleases.…”
Section: The Apoptotic Effects Of Co-treatment With Biogenic Aunps An...mentioning
confidence: 99%
“…The APO-DIRECT TM assay c used to label these DNA fragments with FITC-dUTP using the TdT enzyme, whi corporates FITC-dUTP into the 3′-hydroxyl-DNA ends of the DNA fragments fou apoptotic cells [32]. The current study assessed DNA fragmentation in cells treated HBE, Low DOX (1.56 µg/mL), MGF-AuNPs, HB-AuNPs, MGF-AuNPs-DOX The activation of endonucleases during apoptosis results in the fragmentation of nuclear DNA [31]. In the later steps of cell death, chromosomal DNA is cleaved into smaller fragments through the action of endonucleases.…”
Section: The Apoptotic Effects Of Co-treatment With Biogenic Aunps An...mentioning
confidence: 99%